G Protein-coupled Receptors and Resistance to Inhibitors of Cholinesterase-8A (Ric-8A) Both Regulate the Regulator of G Protein Signaling 14 (RGS14)·Gα(i1) Complex in Live Cells - Vellano, Christopher P. (American Society for Biochemistry and Molecular Biology, 2011)
Regulator of G protein Signaling 14 (RGS14) is a multifunctional scaffolding protein that integrates both conventional and unconventional G protein signaling pathways. Like other RGS (regulator of G protein signaling) proteins, RGS14 acts as a GTPase accelerating protein to terminate conventional Gα(i/o) signaling. However, unlike other RGS proteins, RGS14 also contains a G protein regulatory/GoLoco motif that specifically binds Gα(i1/3)-GDP in cells and in vitro. The non-receptor guanine nucleotide exchange factor Ric-8A can bind and act on the RGS14·Gα(i1)-GDP complex to play a role in unconventional G protein signaling independent of G protein-coupled receptors (GPCRs). Here we demonstrate that RGS14 forms a Gα(i/o)-dependent complex with a G(i)-linked GPCR and that this complex is regulated by receptor agonist and Ric-8A (resistance to inhibitors of cholinesterase-8A). Using live cell bioluminescence resonance energy transfer, we show that RGS14 functionally associates with the α(2A)-adrenergic receptor (α(2A)-AR) in a Gα(i/o)-dependent manner. This interaction is markedly disrupted after receptor stimulation by the specific agonist UK14304, suggesting complex dissociation or rearrangement. Agonist-mediated dissociation of the RGS14·α(2A)-AR complex occurs in the presence of Gα(i/o) but not Gα(s) or Gα(q). Unexpectedly, RGS14 does not dissociate from Gα(i1) in the presence of stimulated α(2A)-AR, suggesting preservation of RGS14·Gα(i1) complexes after receptor activation. However, Ric-8A facilitates dissociation of both the RGS14·Gα(i1) complex and the Gα(i1)-dependent RGS14·α(2A)-AR complex after receptor activation. Together, these findings indicate that RGS14 can form complexes with GPCRs in cells that are dependent on Gα(i/o) and that these RGS14·Gα(i1)·GPCR complexes may be substrates for other signaling partners such as Ric-8A.